Methodological and practical foundations for the transformation of operational activities of enterprises in the field of construction engineering and management consulting - CHUPRYNA, Khrystyna; HERASYMCHUK, Oleksandr; MAKEIEV, Dmytro; KRYVDA, Kyrylo (Ways to Improve Construction Efficiency, 2025)
The transformation of operational activities of enterprises in the field of construction engineering and management consulting is a pressing issue driven by increasing competition, dynamic technological development, and changes in the regulatory environment. The methodological foundations of this transformation include systemic analysis, which allows identifying bottlenecks in current business processes, and strategic management aimed at forming long-term competitive advantages. The application of business process reengineering concepts ensures the optimization of operational activities through redistribution and automation. The practical aspects of transformation involve the implementation of digital technologies such as information and communication systems, artificial intelligence, big data, and cloud computing. These contribute to improved managerial decision-making, enhanced project execution efficiency, and greater flexibility in interactions with clients and partners. In construction engineering, the transformation of operational activities occurs through the introduction of BIM technologies, which enable real-time modeling of project solutions, risk analysis, and cost minimization at the design stage. In management consulting, transformation includes adapting business models to new market conditions, expanding service offerings through the integration of digital platforms, and utilizing analytical methods for trend forecasting. Moreover, a significant impact on transformation processes is exerted by changes in organizational culture, which involve engaging personnel in digitalization processes, developing new competencies, and applying modern knowledge management methods. Tools ensuring effective transformation include a performance indicator system (KPI) that allows monitoring and evaluating changes in operational activities, as well as project management methodologies such as Agile and Lean, which contribute to greater adaptability to changing market conditions. Also important is the involvement of external experts and consulting firms, which provide an independent assessment of the current state of the enterprise and develop recommendations for further optimization. Compliance with regulatory requirements and international standards is key to ensuring sustainable development and aligning transformational changes with the modern demands of the industry. As a result of implementing a comprehensive approach to the transformation of operational activities, enterprises achieve increased efficiency, reduced operational costs, improved stakeholder interactions, and strengthened market positions.